Isotopic analysis (δ13C, δ18O) of Pleistocene megafauna in Brazilian Intertropical Region: paleoecological and paleoenvironmental interpretations - Pansani, Thaís Rabito (Universidade Federal de São Carlos, 2019)
By paleoecological reconstruction based on carbon isotopic analysis in Bahia State and Mato Grosso do Sul State, recently inserted in the Brazilian Intertropical Region (BIR), it was possible to infer ecological aspects of megamammals from these area, as well as the resources consumed (plants C3 and C4), niche width and niche overlaps between species. The organization of the ecological dynamics of the animals studied in Mato Grosso do Sul State is related of Holmesina paulacoutoi with the highest niche width, with a balanced diet, while Toxodon platensis is the one with the narrowest niche width, presenting high consumption of C4 grasses. Glyptotherium sp. and Eremotherium laurillardi showed balanced diet of C3 and C4 plants. In Bahia State, N. platensis presented the highest niche width, with mixed diet, and Equus neogeus the narrowest one, with an exclusive C4 diet. Consequently, the niche overlap for these both individuals was the lowest. E. laurillardi and T. platensis presented mixed-feeding diets, with predominance of C3 plants, while Palaeolama major predominance of C4 grasses. The oxygen values showed a relevant climatic difference in both areas, being able to infer that in Bahia State the environmental conditions were drier and hotter than in Mato Grosso do Sul State, during some age of the late Pleistocene. Within a notorious difference in the feeding behavior found in one of the common species of each localities (T. platensis), the great ecological plasticity of this species is recognized, as well as it is possible to explore possible ecological pressures and environmental dynamics that occurred in Brazil during specific paleoclimate moments in the late Pleistocene, characterizing behavioral changes and ecological strategies of its megamammals communities.
Análises isotópicas (δ13C, δ18O) de megafuana pleistocênica na Região Intertropical Brasileira: interpretações paleoecológicas e paleoambientais
Keywords: Paleoecologia; Largura de nicho; Paleoclima; Estratégias ecológicas; Paleoecology; Niche width; Paleoclimate; Ecological strategies; CIENCIAS BIOLOGICAS::ECOLOGIA